Rancang Bangun Alat Uji Kompresor Torak sebagai Media Pembelajaran - Amrullah - Amrullah; Amirudin Amirudin (Jurnal Teknologi Terpadu, 2018)
Training kit an important role as a equipment for creating effective teaching and learning process.Training kit of reciprocating compressor is expected to facilitate students in understanding the theory and practice subjects related to the compressor. Compressor is a machine to increase air pressure by compressing air from the atmosphere. In simple terms the working principle, pressure and volume changes in a reciprocating compressor can be described in the form of a P-V diagram. The purpose of this study is to generate instructional media so that it understood the working principle and tested on reciprocating compressor one stage and two stages. The research method begins with the design of tools that are simulated visually through solidwork software, component preparation, assembly of learning media and equipments testing. The resulting frame is 1100 mm long, 600 mm wide and 800 mm high. The v-belt type is used according to the v-belt length of 41 inches for the one-level and 53-inch compressors for the two-level compressor. The diameter of the driven pulley also affects the rotation of the compressor shaft (N), the greater the diameter of the pulley then the shaft rotation also decreases. In addition to the rotation difference of the compressor shaft (N) which affects the piston displacement value, the number of piston also affects the Qth value. The reservoir used was 38 liters and was tested for 8 minutes. At a two stages compressor, the resulting pressure is higher at 7.4 bar and on the compressor one pressure level is generated at 7.2 bar. The value of piston displacement (Qth) is 7.188 x 10-2 m3 / min for one level compressor and 8,115x10-2 m3 /min for two level compressor.